Museum DoorDacht 8 : Dirk Skreber / Albert Saverys / Benoît van Innis / Wade Guyton / Peter Buggenhout / Francesco Gennari / Verzameling Wilfried & Yannick Cooreman / Robert Devriendt / Robert Grober / Julião Sarmento / Luc Tuymans. - Imdahl, Georg; Museum Dhondt-Dhaenens, Deurle; Eeckhout, Tanguy; Meskens, Ann; Funcke, Bettina; Schwarz, Dieter; Amy, Michaël; Holthof, Marc (Deurle : Museum Dhondt-Dhaenens, 2009)
Skreber, Dirk ; Saverys, Albert / van Innis, Benoît ; Guyton, Wade ; Buggenhout, Peter ; Gennari, Francesco ; Verzameling Wilfried & Yannick cooreman ; Devriendt, Robert ; Grober, Robert ; Sarmento, Juliao ; Tuymans, Luc ; Schütte, Thomas
Schenking MDD
Tijdschrift over het MDD en haar tentoonstellingen en projecten.
kunstcatalogus